CXCL-10 in Cerebrospinal Fluid Detects Neuroinflammation in HTLV-1-Associated Myelopathy with High Accuracy - Samya Jezine Da Silva; Mauro Jorge Cabral-Castro; Luiz Claudio Faria; Carolina Rosadas; Maria Fernanda Lopes de Araújo; Ana Caroline Soares Dutra; Yoshihisa Yamano; Graham Taylor; Marzia Puccioni-Sohler (Viruses)
Background and Objectives: HTLV-1-associated myelopathy (HAM) is a chronic progressive inflammatory disease of the spinal cord. This study assesses the diagnostic accuracy of the neuroinflammatory biomarkers neopterin and cysteine-X-cysteine motif chemokine ligand 10 (CXCL-10) in cerebrospinal fluid (CSF) for HAM. Methods: CSF samples from 75 patients with neurological disorders—33 with HAM (Group A), 19 HTLV-1-seronegative with other neuroinflammatory diseases (Group B), and 23 HTLV-1-seronegative with non-neuroinflammatory diseases (Group C)—were retrospectively evaluated. CSF examination included routine analysis, neopterin, and CXCL-10. The diagnostic potential of the biomarkers was evaluated using receiver operating characteristic curves. Results: Higher white cell counts and concentrations of protein, neopterin, and CXCL-10 in CSF were detected in group A (patients with HAM) and group B (p < 0.05). Neopterin showed good accuracy for HAM (A) (cut-off 15 nmol/L, 80% sensitivity, 74% specificity) and other neuroinflammation (group B) (cut-off 20 nmol/L, 79% sensitivity, 83% specificity). CXCL-10 demonstrated the highest accuracy in both groups, with Group A (cut-off 110 pg/mL, 97% sensitivity, 96% specificity) and Group B (cut-off 220 pg/mL, 100% sensitivity, 100% specificity). Conclusions: Neopterin and CXCL-10 in CSF are accurate biomarkers for detecting neuroinflammation, including HAM. CXCL-10, in particular, is the superior biomarker for both chronic and acute neuroinflammatory diseases.